An investigation into the nutritional composition and cost of gluten‐free versus regular food products in the UK. Issue 1 (29th August 2017) - Fry, L.; Madden, A. M.; Fallaize, R.
Abstract: Background: The gluten‐free (GF) food market has expanded considerably, although there is limited comparative evidence for the nutritional quality and cost of GF food products. The present study aims to compare the nutrient composition and cost of GF and gluten‐containing (regular) foods across 10 food categories in the UK. Methods: Nutritional information and the cost of GF foods available in the UK ( n  =   679) and comparable regular foods ( n  =   1045) were systematically collected from manufacturer and supermarket websites. Foods were classified using UK front‐of‐pack labelling for content of fat, saturated fat, sugar and salt and nutrient content, and cost per 100 g were identified and compared between GF and regular foods. Results: Overall, more GF foods were classified as containing high and medium fat, saturated fat, sugar and salt than regular foods, although this was not universally consistent. More GF bread and flour products contained high fat and sugar, whereas fewer GF crackers contained high fat and sugar compared to regular foods. High salt content was found more frequently in GF than regular products. On average, GF products were 159% more expensive than regular (£0.44/100 g versus £1.14/100 g). GF items were also more likely to be lower in fibre and protein content than regular foods. Conclusions: Differences exist in the nutritional composition of GF and regular food. GF food is unlikely to offer healthier alternatives to regular foods, except for those who require a GF diet for medically diagnosed conditions, and it is associated with higher costs.